2022
DOI: 10.3390/cosmetics9010014
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant, Antimicrobial, and Antiaging Activities of Ethanolic Seed Extracts of Four Mucuna Species

Abstract: The investigation into promising botanical materials for natural cosmetics is expanding due to environmental and health awareness. Here, we aimed to evaluate the phytochemical substances and the potential skin-related pharmacological activities of four Mucuna seeds, namely M. gigantea (Willd.) DC. (MGG), M. interrupta Gagnep. (MIT), M. monosperma Wight (MMM), and M. pruriens (L.) DC. (MPR), belonging to the Fabaceae family. In methodology, the Mucuna seeds were authenticated using morphological and molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…The flow rate was 0.1 µL/min, and detection was performed at 210 nm. L-DOPA analysis of MW, ME, and MA was identified by comparing the retention time of L-DOPA, a standard material, under the same analysis conditions [18,19].…”
Section: Ultra-performance Liquid Chromatography (Uplc)mentioning
confidence: 99%
“…The flow rate was 0.1 µL/min, and detection was performed at 210 nm. L-DOPA analysis of MW, ME, and MA was identified by comparing the retention time of L-DOPA, a standard material, under the same analysis conditions [18,19].…”
Section: Ultra-performance Liquid Chromatography (Uplc)mentioning
confidence: 99%
“…Jimoh et al reported that M. pruriens seed aqueous extract contained 12 mg GAE/g extract and 3.18 mg QE/g extract [ 31 ]. Theansungnoen et al reported that the total phenolic compounds in Thai mucuna seed extract was 21.78 ± 3.58 mg GAE/g extract and total flavonoid content found in this plant seed was 423.48 ± 6.71 mg QE/g extract [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The four peaks consist of OH stretch (3300-3200 cm -1 ), Aromatic C-H sp 2 bend (3100-3000 cm -1 ), C=O stretch (1700-1600 cm -1 ), and Alkoxy C-O stretch (1100-1000 cm -1 ) (Beauchamp, 2017). A particular compound that have abundant antioxidant activity in GTE is flavonoid monomers which is known as catechins in the form of epigallocatechin-3-gallate and epicatechin-3-gallate compounds (Theansungnoen et al, 2022). The catechin compound is a polyphenol that contains an OH-group, C-H sp 2 aromatic group, carbonyl group (C=O), an alkoxy group (C-O).…”
Section: The Chemical Properties Of Edible Film Fortified With Gtementioning
confidence: 99%